Pan School Looking for New Home - Unknown (Guardian)
Trinity All Generations Steel (TAGS) and School of the Arts is an ongoing community outreach programme established in 1994. The school offers music education for youth in the Port-of-Spain area and its environment, at little cost. TAGS has been unceremoniously thrown out of the Cathedral Church of the Holy Trinity and is now seek an alternative location.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Music -- Instruction and study -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago